Pengaruh Leverage dan Capital Expenditure terhadap Nilai Perusahaan dengan Return on Assets sebagai variabel intervening pada Perusahaan Consumer Non-Cyclicals subsektor Food and Beverage yang terdaftar di BEI Periode 2020-2024 - Dinda Risma Permata Sari; Jhon Veri; Putri Nadia (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of Leverage and Capital Expenditure on firm value with Return on assets (ROA) as an Intervening Variable in Consumer Non-Cyclicals Food and Beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used was purposive sampling, resulting in a sample of 28 companies from a population of 98 firms over a five-year observation period. The data analysis methods employed were panel data regression and path analysis, processed using EViews 13 software. The results indicate that leverage has an effect on Return on Assets (ROA), while Capital Expenditure does not affect Return on Assets (ROA). Leverage is proven to have an effect on Firm Value, whereas Capital Expenditure does not affect Firm Value, and Return on Assets (ROA) does not affect Firm Value. Furthermore, the results of the path analysis show that Leverage does not affect Firm Value through Return on Assets (ROA) as an Intervening Variable, and Capital Expenditure also does not affect Firm Value through Return on Assets (ROA) as an Intervening Variable